The Structure of Space and its Impact on Interplanetary Travel and Answers to Fundamental Cosmological Questions - Sobolewska, Natalia Julia; Sobolewska, Joanna Paulina; Sobolewski, Marek Juliusz; Sobolewski, Michał Amadeusz; Sobolewski, Dariusz Stanisław (JOURNAL OF ADVANCES IN PHYSICS, 2022)
The article presents the far-reaching implications of the theory entitled "Theory of Space" (Sobolewski D. S., Theory of Space, 2016) (Sobolewski D. S., Theory of Space, 2017) (Sobolewski D. S., Theory of Space, 2022 - new unpublished edition) and of the publication "New Generations of Rocket Engines" (Sobolewska, Sobolewska, Sobolewski, Sobolewski, & Sobolewski, 2021). Among others, it presents the shape of curved space in E4 for selected planets of the solar system and the Sun, taking into account boundary hypersurfaces and gravitational interactions. The existence of space tunnels was analysed and the perspective of new technologies enabling interplanetary travel was outlined. Furthermore, due to the revealed structure of space, cosmological issues including the existence of other Universes and possible effects of their interactions are addressed. The constant Gdańsk was also introduced GGdańsk which, together with the introduced equation, makes it possible to determine the maximum immersion depth of an astronomical object of mass M.